Evaluering van gesindheid in kliniese onderrig - A.M. Venter (AOSIS, 1982)
The affective dimension of nursing - which involves attitudes, values and interests - is a very important one and should be evaluated in the clinical area where the student nurse deals with the real situation. Evaluations of the affective dimension are currently often subjective value judgements. It is essential that affective objectives be identified for each learning situation and that relevant, valid and reliable instruments be designed to measure their attainment objectively. The impact of affective elements, in both the student and evaluator, in the clinical situation must however also be kept in mind. Attention must be given to personal relationships in clinical nursing to guard against the threat of technology to humanism in nursing.